The effectiveness of the ASA micro finance scheme in fostering sustainability and viability on the micro finance program of the Jaime V. Ongpin Foundation, Inc. - Abaricio, Erika S.; Banayat, Daryll Erick N. (2008)
The Jaime V. Ongpin Foundation Incorporated (JVOFI) is a foundation established in 1980 by a long time mining company and from the time of their existence started a micro finance program that caters to women. Its micro finance program is aimed at empowering women and at the same time providing accessible loans to people who are not able to loan from banks that require certain collateral. The study assessed how JVOFI , as a non-profit organization, sustains their micro finance operations and programs with the aid of the adopted ASA scheme in 2011. The researchers looked into the system to understand how it works and how JVOFI conducts their transactions with clients who are not able to provide collateral for their loans. The researchers conduct an interview with a representative from JVOFI to ask their processes and activities in the micro finance program. An administrative officer was the preferred representative because she has greater information to the entirety of the program. At the same time, the researchers interviewed at least 10 people who served as a counter-checks for the responses generated from the representative of JVOFI. The researchers also conducted interviews with some of the JVOFI's clients that imparted their experience in the use of loans and how far have they gone in using their availed loans. The responses reflected the impact of JVOFI'S micro finance program to its clients and also take part in supplementing other findings generated from the representative of JVOFI. The researchers also used the financial statements of JVOFI and conducted a secondary data analysis to know how well the micro finance program is performing with regard to their collection efficiency, liquidity and sustainability. The researchers looked into their assets, repayment rates, liabilities, portfolio at risks, income, past dues, etc. Lastly, the research came up with conclusions that expound the strengths and weakness of JVOFI's developing micro finance program. Recommendations were made to give a more concrete solution to problems found during the analyses of data and provide an open door for improvement with in the institution -- Author's abstract.
Thesis (Bachelor of Arts) -- University of the Philippines Baguio, 2008.
Includes bibliographical references.
Keywords: Jaime V. Ongpin Foundation Incorporated (JVOFI); Microfinance -- Philippines -- Baguio City